Positive Findings Regarding a New Trend in University Architecture Evaluating Student Impressions of an Innovative Academic Building - Nguyen, Son; Kennedy, Kristin; Zywiak, William H. (Archives of Business Research, 2018)
Bryant University recently opened a spectacularly visually appealing, new building, the Academic Innovation Center (AIC). It was designed to promote innovative problem solving classroom experiences for business and liberal arts students alike with a spacious and wide open feeling. Bryant is among a group of other universities who are turning to radically different building design. Kamal (et.al.) in a lengthy white paper captures the essence of why universities are turning towards such novel architecture [1]. Students and faculty alike are enjoying the pleasure of working in such an aesthetically pleasing place. The intentions of this paper were to capture the emotions and perceptions of students regarding their impressions of the new building as it just opened, and capture perceptions on whether the new design really did effect a feeling of engagement and collaboration. Upon the opening semester, we surveyed the students that fall with a pre and post survey (September and December) regarding perceptions of engagement, collaboration, and enjoyment. We hoped that the administered survey would illustrate that the new space did indeed foster a feeling of academic success and bolster a new excitement for learning with the students. Varied statistical techniques were used to capture diverse results.